Effectiveness of Common Washing Methods in Eliminating Ascaris lumbricoides Contamination from Fresh Vegetables Collected from Farms in Brack Alshatti - Alshareef , Shaheerah; Bernawi, Abdulkadir; Abdulsalam, Awatif (Wadi Alshatti University Journal of Pure and Applied Sciences, 2026)
Fresh vegetables provide important nutritional value for humans; however, they can become contaminated with enteric parasitic pathogens at various stages, from cultivation to consumption. Therefore, this study aimed to investigate the contamination of Ascaris lumbricoides in fresh vegetables collected from farms in Brack Al-Shatti, Libya, and to determine the most effective method for removing Ascaris lumbricoides egg contamination from vegetables. A total of 70 fresh vegetable samples were randomly collected from vegetable farms in Brack Alshatti. The vegetables included green onion, lettuce, rocket, parsley, chard, carrot, and turnip. Different washing methods were applied, including 5% vinegar, 10% salt, and 20% lemon solutions, in addition to washing with tap water. Microscopic examination for the presence of A. lumbricoides eggs was performed using a direct wet mount technique. Overall contamination with A. lumbricoides was detected in 22.9% (16/70) of the vegetable samples. After washing with tap water, parasitic contamination was detected in 20.0% (14/70) of the samples. Washing with 10% salt reduced the contamination rate to 11.0% (8/70), while washing with 20% lemon reduced it to 4.3% (3/70). The lowest contamination rate was observed after washing with 5% vinegar, at 2.9% (2/70). The results showed persistent contamination with A. lumbricoides in turnip and lettuce when all washing methods were applied. After washing with 10% salt, no contamination was detected in green onion. Furthermore, no contamination was observed in green onion, carrot, rocket, parsley, or chard after washing with 5% vinegar or 20% lemon. These findings highlight vinegar as a superior washing agent, effectively eliminating parasitic contamination while offering a safe and broadly effective solution.